Evidence for Recipient-Derived Cells in Peribiliary Glands and Biliary Epithelium of the Large Donor Bile Ducts After Liver Transplantation - de Jong, Iris E. M.; Sutton, Michael E.; van den Heuvel, Marius C.; Gouw, Annette S. H.; Porte, Robert J. (Frontiers in Cell and Developmental Biology, 2020)
Chimerism after orthotopic liver transplantation (OLT) has largely been investigated in intrahepatic cellular constituents. However, little is known about chimerism in the extrahepatic and large intrahepatic bile ducts. Our aim was to evaluate the presence and extent of chimerism after OLT in the peribiliary glands (PBG) and the luminal epithelium of the large donor bile ducts. For this study, we examined six extrahepatic and large intrahepatic bile ducts from livers that were re-transplanted. In all cases there was a sex-mismatch between donor and recipient (female donor organ and male recipient), which allowed to discriminate between donor- and recipient-derived cells. Specimens from female to female transplants were used as negative controls and male to male transplants as positive controls. Fluorescence in situ hybridization (FISH) for Y and X chromosomes was performed and the percentage of XY positive cells was determined among biliary epithelial cells. Immunohistochemistry was used to correlate chimerism with histological features. Cholangiocellular chimerism in all studied specimens ranged from 14 to 52%. The degree of chimerism was not associated with biliary damage. Marked chimerism was present at 5 days post-OLT. Ki-67-positivity was detected in 1-8% of the epithelial cells at the time of liver re-transplantation, and this correlated inversely with the degree of chimerism. Recipient-derived cholangiocytes are present in the large bile ducts of the donor liver after OLT. The presence of chimerism in the large bile ducts suggests that recipient-derived cells may play a role in biliary regeneration following ischemia-induced injury during OLT.